2003
DOI: 10.1021/bi026979d
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic Acid Prevents Bax-Induced Membrane Perturbation and CytochromecRelease in Isolated Mitochondria

Abstract: Bax is a potent pro-apoptotic member of the Bcl-2 protein family that localizes to the mitochondrial membrane during apoptosis. Tauroursodeoxycholic acid (TUDCA) modulates the apoptotic threshold, in part, by preventing Bax translocation both in vitro and in vivo. The mechanisms by which Bax induces and TUDCA inhibits release of cytochrome c are unclear. We show here that recombinant Bax protein induced cytochrome c release in isolated mitochondria without detectable swelling. Coincubation with TUDCA prevented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 62 publications
4
75
0
1
Order By: Relevance
“…This suggestion is also consistent with the independent observation that transient expression of the phosphorylated form of eIF2␣ induced a preconditioned, stress-resistant state that rendered cells less susceptible to other stress-induced signals (34). It is also worth noting that TUDCA has been shown to stabilize mitochondrial membranes and thereby to reduce apoptosis in isolated rat hepatocytes (35). Whether such a membrane-stabilizing effect occurs within enterocyte mitochondria following parenteral TUDCA administration is unknown.…”
Section: Discussionsupporting
confidence: 83%
“…This suggestion is also consistent with the independent observation that transient expression of the phosphorylated form of eIF2␣ induced a preconditioned, stress-resistant state that rendered cells less susceptible to other stress-induced signals (34). It is also worth noting that TUDCA has been shown to stabilize mitochondrial membranes and thereby to reduce apoptosis in isolated rat hepatocytes (35). Whether such a membrane-stabilizing effect occurs within enterocyte mitochondria following parenteral TUDCA administration is unknown.…”
Section: Discussionsupporting
confidence: 83%
“…The involvement of a5b1 integrin and PI3K/AKT signaling was ruled out because TUDCA-mediated protection from TNF-induced caspase-3 activation is insensitive toward blocking PI3K by wortmannin or the a5b1 integrinblocking hexapeptide GRGDSP. In addition, TUDCA acts on the permeability of the mitochondrial membrane and the concomitant release of cytochrome c. 33 In HT29 cells, similar protection from TNF-induced cytochrome c release from the mitochondria (data not shown), as well as caspase-9 activation, was observed. Finally, TUDCA could also interfere in cell membrane composition or structure and inhibit crosslinking of transmembrane TNF receptors.…”
Section: Tudca Prevents Intestinal Epithelial Cell Death D Laukens Et Almentioning
confidence: 75%
“…Steer's 33 group recently reported that UDCA can prevent insertion of recombinant Bax into isolated rat liver mitochondria, thereby providing a mechanism for protection from apoptosis by UDCA. In studies to be reported elsewhere, we could not duplicate this effect with L1210 cells and recombinant Bax, unless the Bax was first 'activated', 34 that is, by exposure to octyl glucoside.…”
Section: Discussionmentioning
confidence: 99%